Clinical course of patients relisted for orthotopic heart transplantation: A national study - David Rekhtman, BS; Amit Iyengar, MD, MSE; Nikhil Ganjoo, BA; Cindy Song, BA; Noah Weingarten, MD; Max Shin, MD; Michaela Asher, MPhil; John DePaolo, MD, PhD; Marisa Cevasco, MD, MPH; Pavan Atluri, MD (JHLT Open)
Background: The clinical course in patients relisted for heart transplant at a different transplant center is poorly understood. We sought to describe the baseline characteristics, outcomes, and hospital selection of relisted patients by comparing their clinical status at the time of initial and subsequent listing. Methods: The United Network for Organ Sharing database was queried for adults listed for first-time isolated heart transplantation between October 18, 2018 and September 30, 2023. Patients delisted from their original transplant center due to relisting at another center were identified. Upon propensity score matching, waitlist and post-transplant outcomes were compared between single-listing and relisted patients. The same characteristics and center volume at the time of initial listing and subsequent relisting were compared. Center quality based on aggregated 1-year mortality was also assessed. Results: Two hundred and seventeen patients were delisted and subsequently relisted. Upon propensity score matching, no significant differences were found between single-listing and relisted patients with regard to waitlist outcomes (all p > 0.05). On subsequent listing, relisted patients had more severe functional limitations (10% vs 23%, p < 0.001), higher status (p < 0.001), and were more likely to be relisted at a higher volume (45% vs 73%, p < 0.001) and better-performing transplant center (p = 0.017). Conclusions: Although waitlist outcomes were similar between single-listing and relisted patients, at the time of relisting, patients were more likely to have severe functional limitations coinciding with higher listing statuses. Further work is needed to determine the underlying motivators for relisting.